History of the bolshevik party from the beginnings to february 1917 : a popular outline - Zinovjev, Grigori (New York : Labor Publications, 1983)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: bolsjewisme; Sovjet-Unie.